Frameworks compiled from declarations: a language‐independent approach. (3rd June 2016) - van der Walt, Paul; Consel, Charles; Balland, Emilie
Summary: Programming frameworks are an accepted fixture in the object‐oriented world, motivated by the need for code reuse, developer guidance and restriction. A new trend is emerging where frameworks require domain experts to provide declarations using a domain‐specific language, influencing the structure and behaviour of the resulting application. These mechanisms address concerns such as user privacy. Although many popular open platforms such as Android are based on declaration‐driven frameworks, current implementations provide ad hoc and narrow solutions to concerns raised by their openness to non‐certified developers. Most widely used frameworks fail to address serious privacy leaks and provide the user with little insight into application behaviour. To address these shortcomings, we show that declaration‐driven frameworks can limit privacy leaks, as well as guide developers, independently from the underlying programming paradigm. To do so, we identify concepts that underlie declaration‐driven frameworks and apply them systematically to an object‐oriented language, Java and a dynamic functional language, Racket. The resulting programming framework generators are used to develop a prototype mobile application, illustrating how we mitigate a common class of privacy leaks. Finally, we explore the possible design choices and propose development principles for developing domain‐specific language compilers to produce frameworks, applicable across a spectrum of programming paradigms. Copyright © 2016 John Wiley & Sons, Ltd.